2012
DOI: 10.2174/156720112798375989
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Preferentially Target Cancer Stem Cells; Role of Monocytes in Protection Against NK Cell Mediated Lysis of Cancer Stem Cells

Abstract: Mounting effective anti-tumor immune responses by cytotoxic effectors is important for the clearance of tumors. However, accumulated evidence suggests that the cytotoxic function of immune effectors is largely suppressed in the tumor microenvironment by a number of distinct effectors and their secreted factors. The aims of this review are to provide a rationale and potential mechanism for immunosuppression in cancer, and to demonstrate the significance of such immunosuppression in cellular differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 0 publications
2
55
0
Order By: Relevance
“…One of these reports shows that tumor cells in the peritoneal cavity express PD-L1 and escape from CD8ϩ cytotoxic lymphocytes (40). Previously, studies reported that NK cells can recognize and kill tumor cells in an MHC-independent manner and that allogeneic NK cells preferentially target cancer stem cells (25,41). In this study, we found that cancer cells experienced EMT and acquired a CSC phenotype when exposed to malignant PE/ascites.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…One of these reports shows that tumor cells in the peritoneal cavity express PD-L1 and escape from CD8ϩ cytotoxic lymphocytes (40). Previously, studies reported that NK cells can recognize and kill tumor cells in an MHC-independent manner and that allogeneic NK cells preferentially target cancer stem cells (25,41). In this study, we found that cancer cells experienced EMT and acquired a CSC phenotype when exposed to malignant PE/ascites.…”
Section: Discussionsupporting
confidence: 50%
“…3E), two putative CSC markers, protecting cancer stem cells from chemotherapeutic agents (24). On the other hand, recent reports show that allogeneic NK cells preferentially target cancer stem cells (25). To test whether malignant PE/ascites influence the susceptibility to cytotoxicity of NK cells, we analyzed malignant PE/ascites-cultured tumor cells for their susceptibility to IL-2/IL-15-activated NK cell populations derived from healthy donors.…”
Section: Malignant Pe/ascites Induce Emt In Vivo and In Vitro-mentioning
confidence: 99%
“…Hence, targeting stem cells may be of prime importance for long-term remission of the tumor. Immunotherapy may be a promising therapeutic option to target these cells and generate a long lasting memory response (47).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that host immune system has the ability to recognize CSCs and provoke an immune response. Early studies in HNSCC have shown that NK cells may preferably target CSCs (35). In addition, CSCs interact with tumor microenvironment.…”
Section: Immune System and Cancer Developmentmentioning
confidence: 99%